The relationship between accessibility to internet and the elearning effectiveness of students in UiTM Shah Alam / Mona Syafika Monir, Norshuhada Amsari and Fatin Nor Syzwani Saib - Monir, Mona Syafika; Amsari, Norshuhada; Saib, Fatin Nor Syzwani (2011)
The purpose of this study was to investigate the Relationship between Accessibility to Internet and the E-Ieaming Effectiveness of Students in UiTM Shah Alam. The scope of the study was from two programs, which Facu1ty of Computer Science and Faculty of Information Studies. In this study, the researchers used disproportionate stratified random sampling technique. The instruments were adopted from Krejcie and Morgan (1970). This correlation study used survey questionnaires which have been distributed to 74 respondents and the return rate was 100%. Data analyze were done by using PSAW 18.0. This study showed that the majority of the respondents agreed that elements of using E-Ieaming as the method to easy study were effectiveness. From the finding, there were some recommendations given to the organization. First, top management should improve the knowledge about E-Iearning benefits to the students and lecturers. It is also highlighted that top management should increase the using of E-Ieaming modules because it could contribute to their highest affective commitment. The possible reason and the implications of these findings will be elaborated and discussed.